Feasibility of Clinical Hypnosis for Test Anxiety in First-Year Medical Students - Hammer, Christian; Scholz, Michael; Bischofsberger, Larissa; Paulsen, Friedrich; Burger, Pascal H. M. (International Journal of Clinical and Experimental Hypnosis, 2020)
The purpose of this pilot study was to characterize test anxiety among first-year medical students at the University of Erlangen-Nürnberg and to test clinical hypnosis as a possible intervention. The “Prüfungsangstfragebogen,” a shortened and revised German version of the Test Anxiety Inventory, was used to estimate test anxiety. It was administered 3 times: at the commencement of winter term 2017/18 and 2 days prior to each of 2 mandatory oral anatomy exams. The test-anxiety categories emotionality, worry, interference, and lack of confidence were evaluated. The effect of clinical hypnosis on test anxiety was estimated. The global test anxiety and lack of confidence scores were reduced significantly over time in the group that underwent clinical hypnosis but not in the control group. Direct comparisons of hypnosis vs. control group yielded no statistically significant differences in the test anxiety scores.
CRIS-Team Scopus Importer:2020-08-28